Naringin Regulates the Growth and Apoptosis of Ovarian Cancer Cells via the TGF-β Signaling Pathway: A Prospective Laboratory Based Study - Xiaoni Zhou; Ying Yu; Bingqing Xie; Tingtao Chen; Liping Cai (IMR Press, 2024)
Background: Traditional Chinese medicine (TCM) exhibits anti-tumor capabilities. This study explored the anti-tumor activity of Naringin in ovarian cancer and the signaling mechanism. Methods: The current investigation comprised the administration of various concentrations of Naringin, paclitaxel, and cisplatin to SKOV3 cells. Following the therapy, the protein expression levels for (TGF-β) and its downstream (Snail1)/(SMAD2) were measured in SKOV3 cells. Finally, small interfering RNA (siRNA) targeting TGF-β was synthesized, and the recombinant plasmid vector overexpressing TGF-β was constructed to detect the mRNA and protein expression of Snail1/SMAD2. The results were verified in animal models. Results: In this study, the expression of TGF-β varied significantly with varying Naringin concentrations. The expression of the downstream Snail1/SMAD2 was also affected. With increasing Naringin concentration, the expression of Snail1/SMAD2 decreased gradually in cells. Moreover, overexpressing TGF-β increased the expression of Snail1/SMAD2 and vice versa. In addition, Naringin further decreased the expression of Snail1/SMAD2 produced by transforming growth factor-β (TGF-β). Consistent outcomes were achieved when TGF-β agonists and inhibitors were employed alongside the inclusion of Naringin in animal models. Conclusions: The results of the present study demonstrated that Naringin suppressed the proliferation of ovarian cancer cells in a manner that depended on the dosage and also triggered programmed cell death (apoptosis) in ovarian cancer cells by activating the TGF-β mediated signaling pathway.